Tranexamic acid and bleeding in patients treated with non-vitamin K oral anticoagulants undergoing dental extraction: The EXTRACT-NOAC randomized clinical trial. - Anna Ockerman; Isabel Miclotte; Maarten Vanhaverbeke; Thomas Vanassche; Ann Belmans; Jan Vanhove; Joeri Meyns; Nasser Nadjmi; Geert Van Hemelen; Patrick Winderickx; Reinhilde Jacobs; Constantinus Politis; et al. (PLoS Medicine)
Background Oral bleeding after dental extraction in patients on non-vitamin K oral anticoagulants (NOACs) is a frequent problem. We investigated whether 10% tranexamic acid (TXA) mouthwash decreases post-extraction bleeding in patients treated with NOACs. Methods and findings The EXTRACT-NOAC study is a randomized, double-blind, placebo-controlled, multicenter, clinical trial. Patients were randomly assigned to 10% TXA or placebo mouthwash and were instructed to use the mouthwash once prior to dental extraction, and thereafter for 3 times a day for 3 days. The primary outcome was the number of patients with any post-extraction oral bleeding up to day 7. Secondary outcomes included periprocedural, early, and delayed bleeding, and the safety outcomes included all thrombotic events. The first patient was randomized on February 9, 2018 and the last patient on March 12, 2020. Of 222 randomized patients, 218 patients were included in the full analysis set, of which 106 patients were assigned to TXA (74.8 (±8.8) years; 81 men) and 112 to placebo (72.7 (±10.7) years; 64 men). Post-extraction bleeding occurred in 28 (26.4%) patients in the TXA group and in 32 (28.6%) patients in the placebo group (relative risk, 0.92; 95% confidence interval [CI], 0.60 to 1.42; P = 0.72). There were 46 bleeds in the TXA group and 85 bleeds in the placebo group (rate ratio, 0.57; 95% CI, 0.31 to 1.05; P = 0.07). TXA did not reduce the rate of periprocedural bleeding (bleeding score 4 ± 1.78 versus 4 ± 1.82, P = 0.80) and early bleeding (rate ratio, 0.76; 95% CI, 0.42 to 1.37). Delayed bleeding (rate ratio, 0.32; 95% CI, 0.12 to 0.89) and bleeding after multiple extractions (rate ratio, 0.40; 95% CI, 0.20 to 0.78) were lower in the TXA group. One patient in the placebo group had a transient ischemic attack while interrupting the NOAC therapy in preparation for the dental extraction. Two of the study limitations were the premature interruption of the trial following a futility analysis and the assessment of the patients' compliance that was based on self-reported information during follow-up. Conclusions In patients on NOACs undergoing dental extraction, TXA does not seem to reduce the rate of periprocedural or early postoperative oral bleeding compared to placebo. TXA appears to reduce delayed bleeds and postoperative oral bleeding if multiple teeth are extracted. Trial registration ClinicalTrials.gov NCT03413891 EudraCT; EudraCT number:2017-001426-17; EudraCT Public website: eudract.ema.europa.eu.